Follow-Up of Advanced Parkinson’s Disease Patients after Clinical or Surgical Emergencies: A Practical Approach - Hélio A. G. Teive; Matheus Gomes Ferreira; Carlos Henrique F. Camargo; Renato P. Munhoz (Parkinson's Disease)
Background. Patients with advanced stage Parkinson’s disease (PD) typically present with a myriad of motor and nonmotor symptoms in addition to comorbidities and, as a consequence, polypharmacy. Objective. To analyze a series of cases of advanced PD in which a clinical or surgical emergency played a trigger role in the irreversible progression of landmarks of the course of the disease. Methods. Data were collected during a 13-month observational period of a cohort of 230 PD patients, in 751 medical appointments. We included a total of 13 (5.65% of the total number) patients with advanced PD defined by Hoehn & Yahr (H&Y) stage ≥3 who presented with various clinical and surgical complications which, with the contribution of drug interventions, led to significant worsening of patients’ overall clinical condition. Results. Hip fractures and infections were the most common complications identified. As part of this scenario, most patients presented with delirium, often requiring treatment with dopamine receptor blocking agents and/or had dopaminergic treatment withdrawn. Upon reassessment after 3 months, all patients remained bed or wheel chair bound (H&Y 5) and presented significant worsening of their UPDRS part III score of at least 10 points (mean 51.5 ± 3.3; paired t-test two-tailed p<0.0001 compared to baseline). The mean dose of levodopa at baseline was 907.7 ± 149.8 mg (600–1200) and significantly higher (paired t-test two-tailed p<0.0001) on follow-up, 1061.5 ± 175.8 mg (700–1300). Conclusion. Clinical and surgical emergencies are major determinants for a progression of PD to more advanced stages.